Characterization of In-Situ TiB/TiC Particle-Reinforced Ti-5Al-5Mo-5V-3Cr Matrix Composites Synthesized by Solid-State Reaction with B4C and Graphite through SPS - Steffen Grützner; Lutz Krüger; Markus Radajewski; Ines Schneider (Metals, 2018)
In-situ TiB/TiC particle-reinforced titanium matrix composites (TMCs) based on a near-β Ti-5Al-5Mo-5V-3Cr alloy (Ti-5553) were synthesized by solid-state reaction with B4C and graphite particles during spark plasma sintering (SPS). In this study, investigations were focused on the influence of the molar TiB:TiC ratio on the mechanical properties of the composites. With respect to the adjustment of the molar TiB:TiC ratio, the formation of stoichiometric TiC or nonstoichiometric TiCy was considered as the literature provides conflicting information in this respect. Furthermore, the solid-state reaction behavior influenced by the matrix alloying elements is discussed in comparison to a pure titanium matrix. The hardness, compressive strength and bending strength of the TMCs were improved successfully due to the TiB and TiC particles maintaining acceptable levels of ductility. However, X-ray diffraction experiments revealed that for the adjustment of the molar TiB:TiC ratio, the stoichiometry of the TiCy particles formed must be considered as nonstoichiometric TiC0.5 resulted from the solid-state reaction of carbon and titanium. Compared to TMCs with pure titanium matrices, more sluggish solid-state reaction kinetics were observed. This was attributed to the matrix alloying elements molybdenum, vanadium and chromium, which formed solid solutions within the reinforcing particles.